Intelligent computing theories and application : 15th International Conference, ICIC 2019, Nanchang, China, August 3–6, 2019, Proceedings, Part I /: 15th International Conference, ICIC 2019, Nanchang, China, August 3–6, 2019, Proceedings, Part I. (2019) - Unknown
No abstract available